Assessment and Comparison of Knowledge and Awareness about Hand Hygiene among Health Care Workers from PHC and Medical College - Amit Pasari1 , Pratibha Deshmukh2 , Sweety Agrawal3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: Present study was conducted to assess and compare the knowledge of hand hygiene (HH)according to WHO guidelines among healthcare workers (HCW) from medical college hospital and primaryhealth care centre (PHC). Improvement in knowledge of HH was assessed after training.Method: Cross-sectional study was conducted in two groups comprising of 167 HCW from a medical collegehospital (GROUP A) and from PHC (GROUP B). The WHO “Hand Hygiene Knowledge Questionnaire”was used to collect data. Multiple choice questions were given to participants before and after trainingprogram for HH.Results: Eighty & eighty seven HCW were recruited in group A & B respectively. Before HH trainingprogram, both the groups had very few people with good knowledge of HH (8.7% in group A & 5.7% ingroup B). After attending the HH training program, there was significant increase in the number of individualshaving good knowledge of HH practise (52.5% & 35.6 % in group A and B respectively, p<0.001 for thegroups).There was significant increase in the mean scores in both groups after HH training from 57.638+12.52% to 75.66 + 12.45%, p <0.001 in GROUP A & 46.66 +18.7% to 64.59 + 18.97%, p<0.001 in Group B.Conclusions: There was low level of awareness about HH practices in studied population. Regular awarenessprogram must be conducted to improve the knowledge of HH. Medical colleges should consider conductingsuch program for all HCW including PHC HCW at regular interval.